Partial amino-acid sequences of human and rabbit C-reactive proteins: homology with immunoglobulins and histocompatibility antigens. - Osmand, A P (1977)
Partial amino-acid sequence analyses of the amino terminus of rabbit C-reactive protein and of a peptide isolated from human C-reactive protein after cyanogen bromide cleavage show an extensive sequence homology between these proteins. Computer analysis detected a distant but significant homology between rabbit C-reactive protein and the CH3 domain of human IgG, In addition, an examination of the limited data available for the amino-acid sequences of human and mouse histocompatibility antigens revealed a similarity between these proteins and C-reactive protein and, therefore, immunoglobulins; These relationships are presented as evidence in support of the hypothesis that C-reactive protein and immunoglobulins share, in addition to functional similarities, a common evolutionary origin with the major histocompatibility antigens.